PSYCHO-PEDAGOGICAL TRAINING AS A COMPONENT OF HIGHER ECONOMIC EDUCATION - Артюшина, М. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article deals with the problem of imperfection substantial component of future economists training.It  shows the importance of psychological and pedagogical training for the formation of a professional important personal qualities of future economists. It’s analysed the psychological and pedagogical training in domestic economic universities. It’s made the comparison with the neighboring countries and identified perspective directions for future improvement